Influência da fase I de compostagem e da esterilização do composto no cultivo de duas linhagens do Pleurotus ostreatus var. Florida - Zanon, André Ricardo [UNESP] (2015)
Pleurotus ostreatus Var. Florida, currently known as white shimeji, is a variety of mushroom that is expanding in Brazilian market mainly owing to its rustic characteristics of cultivation in small and taken areas, factors which attract many farmers for this practice. In Brazil, the short composting with subsequent steam pasteurization and conditioning is the widely used method to obtain the cultivation substrate. There is also another cultivation, although on a small scale, made by aseptic ways which is called axenic culture. The composting and pasteurization used nowadays are based on procedures employed in China, Europe and United States of America, which weather and raw material are different. Therefore it is necessary to make researches that show best ways to manage these stages of mushrooms production in order to obtain more satisfactory results - which embody likewise tests with different lineages looking for those one that present higher biological and productivity efficiency. Assessing the influence of three different composting cycles (6, 4 and 2 days) and compound sterilization (121ºC/1atm for 2 hours) on the production patterns of mushroom (biological efficiency, productivity, incubation period, number and average weight of the bunches collected) it was done an experiment at the mushroom department at Faculdade de Ciências Agrárias de Botucatu, which consists of 8 treatments divided into 2 groups: pasteurization (T1 to T6) x axenic (T7 and T8) ...